Reduction of the erosive potential of a soft drink with polymers and calcium - Kairalla, Cláudia Allegrini; Muniz, Milena Rodrigues; Sakae, Letícia Oba; Nogueira, Fernando Neves; Aoki, Idalina Vieira; Pessan, Juliano Pelim [UNESP]; Borges, Alessandra Bühler [UNESP]; Scaramucci, Taís (Elsevier, 2025)
OBJECTIVES: To evaluate the erosive potential of a soft drink modified with film-forming polymers and calcium on bovine enamel and dentin. METHODS: Sprite Zero Sugar was modified with linear sodium polyphosphate (LPP-10 g/L) and sodium trimetaphosphate (TMP-10 g/L), individually or combined with calcium lactate pentahydrate (CLP-4.35 g/L). Enamel and dentin specimens were randomly assigned into six groups (n = 10/substrate): 1. C- (negative control-no modification); 2. LPP; 3. TMP; 4. LPP+CLP; 5. TMP+CLP; 6. C+ (positive control-CLP). The specimens underwent an erosion-remineralization cycling. Surface loss (SL, in μm) was measured with an optical profilometer. Color and viscosity of the drinks were analyzed. Data were statistically analyzed (α=0.05). RESULTS: For enamel and dentin, LPP significantly reduced the erosive effect of the drink compared to C- (p < 0.001 for both), with reductions of approximately 53 % and 41 %, respectively. TMP showed no significant difference from C- for both substrates. C+ reduced SL by 87 % in enamel and 38 % in dentin when compared to C- (p < 0.001). When CLP was combined with the polymers, in enamel, a 97 % reduction in SL for LPP+CLP and TMP+CLP was observed. In dentin, reductions of 56 % and 48 % were observed for LPP+CLP and TMP+CLP. No significant differences were observed between the groups and the C- regarding color and viscosity (p > 0.05). CONCLUSIONS: All solutions containing calcium lactate (CLP) were effective in reducing the erosive potential of the original soft drink. The combinations of CLP with LPP or TMP significantly enhanced protection, especially for dentin. Notably, LPP alone was effective in minimizing erosion of both enamel and dentin. CLINICAL RELEVANCE: Reducing the erosion potential of soft drinks may benefit non-collaborative individuals with high risk for erosive tooth wear.